Making sense of data I : a practical guide to exploratory data analysis and data mining - Myatt, Glenn J., 1969-; Johnson, Wayne P. (Hoboken, New Jersey : John Wiley & Sons, Inc., 2014)
"A proven go-to guide for data analysis, Making Sense of Data I: A Practical Guide to Exploratory Data Analysis and Data Mining, Second Edition focuses on basic data analysis approaches that are necessary to make timely and accurate decisions in a diverse range of projects. Based on the authors' practical experience in implementing data analysis and data mining, the new edition provides clear explanations that guide readers from almost every field of study. In order to facilitate the needed steps when handling a data analysis or data mining project, a step-by-step approach aids professionals in carefully analyzing data and implementing results, leading to the development of smarter business decisions." --
6.3 Logistic Regression6.4 K-Nearest Neighbors; 6.5 Classification and Regression Trees; 6.6 Other Approaches; Exercises; Further Reading; APPENDIX A ANSWERS TO EXERCISES; APPENDIX B HANDS-ON TUTORIALS; B.1 Tutorial Overview; B.2 Access and Installation; B.3 Software Overview; B.4 Reading in Data; B.5 Preparation Tools; B.6 Tables and Graph Tools; B.7 Statistics Tools; B.8 Grouping Tools; B.9 Models Tools; B.10 Apply Model; B.11 Exercises; BIBLIOGRAPHY; INDEX; END USER LICENSE AGREEMENT
Revised editon of: Making sense of data. c2007.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Data mining; Mathematical statistics; Mathematical statistics; Data mining; COMPUTERS -- General; Data mining; Mathematical statistics; Mathematical statistics; Data mining; Electronic books; Electronic books